On the Unity of Buddhist Tradition: Zen and the Taming of the Bull. Towards the Definition of Buddhist Thought. Essays by Walpola Rahula. - Werner, Karel (Buddhist Studies Review, 1980)
Zen and the Taming of the Bull. Towards the Definition of Buddhist Thought. Essays by Walpola Rahula. Gordon Frazer, London 1978. 160 pp. £6.50.